Assessing Students’ Perceptions of EFL Learners’ Problems and Challenges in Speaking Skills - Dini Riandini (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Speaking is an essential skill for learners of any foreign language, and English is no exception. However, many English as a Foreign Language (EFL) learners experience significant challenges when it comes to speaking skills. This study aims to explore the views of students regarding the difficulties they face in speaking English and to identify potential solutions to these challenges. A case study method was employed, involving twenty-seven university students from Indonesia. The data were collected using questionnaires, which allowed the researchers to gather insights into students' perceptions and experiences with speaking English. The results revealed that the majority of participants, 71.6%, reported facing common difficulties such as the fear of making mistakes, fear of criticism, and general shyness. These emotional barriers significantly hindered their ability to speak confidently in class. Additionally, only 18.5% of the students actively participated in speaking activities during lessons, indicating a lack of engagement in oral communication. A significant number of students (96.3%) felt that they lacked sufficient knowledge of the subject matter, further impeding their ability to speak effectively. Moreover, 81.5% of the students admitted that they preferred to use their mother tongue, which they often spoke during English classes, as it was easier for them. These findings suggest that both emotional and knowledge-related issues play a crucial role in shaping the speaking abilities of EFL learners. The study highlights the need for targeted interventions that address both the emotional barriers and knowledge gaps in order to improve the speaking skills of EFL students.